Hubungan hasil belajar kognitif dan retensi siswa SMA Negeri Taekas pada materi sistem peredaran darah - Paul, Blandina Paul (Jurnal Pendidikan Biologi Undiksha, 2023)
This study aims to determine the relationship between cognitive learning outcomes and retention of Taekas State Senior High School students in the matter of the circulatory system. The research was conducted on January 16-30 2023. The population in this study were all Taekas State High School students consisting of 627 students. The sample of this research was students of class XI MIA 1 and XI MIA 2 of SMA Negeri Taekas which consisted of 50 students. The data were obtained from the post test and retention test which were carried out two weeks after the post test was carried out. Research data were analyzed using SPSS V25 with regression correlation analysis. The results of the study show that there is a significant relationship between cognitive learning outcomes and student retention. The contribution made by cognitive learning outcomes to student retention is 98.2%, with a correlation coefficient of 0.983. Based on the results of the regression test Y = 0.9837x - 8.6278.